2010
DOI: 10.7202/1000316ar
|View full text |Cite
|
Sign up to set email alerts
|

La diversité ethnoculturelle dans les programmes français de sciences et technologie de l’Ontario : une analyse comparative entre le programme de 1998 et celui de 2007

Abstract: Le ministère de l’Éducation de l’Ontario (MEO) a procédé récemment à une réforme des programmes d’enseignement. En vigueur depuis septembre 2008, le nouveau programme de sciences de la 1re à la 8e année prône une éducation antidiscriminatoire. Cette visée se reflète-t-elle dans ce programme? En quoi le nouveau programme se distingue-t-il de l’ancien au chapitre de l’éducation antidiscriminatoire? Pour répondre à ces questions, notre étude propose une comparaison des programmes en français de sciences et techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The results of this article are consistent with previous research that found that multicultural and antiracist content remain poorly integrated into Ontario science curricula (Mujawamariya, 2007;Mujawamariya & Moldoveanu, 2010;Shujah, 1999). Our critical analysis of Ontario's compulsory science curricula revealed that disconnected fragments of MSC could be found in these documents.…”
Section: Discussionsupporting
confidence: 94%
“…The results of this article are consistent with previous research that found that multicultural and antiracist content remain poorly integrated into Ontario science curricula (Mujawamariya, 2007;Mujawamariya & Moldoveanu, 2010;Shujah, 1999). Our critical analysis of Ontario's compulsory science curricula revealed that disconnected fragments of MSC could be found in these documents.…”
Section: Discussionsupporting
confidence: 94%